Observation of the suppressed decay [Lambda]0b→pπ−[mu]+[mu]− - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2017)
The suppressed decay Λ b0 →  pπ− μ+ μ−, excluding the J/ ψ and ψ(2 S) → μ+ μ−resonances, is observed for the first time with a significance of 5.5 standard deviations. The analysis is performed with...